CELIE: A PORTRAYAL OF AN AFRO-AMERICAN WOMAN'S REJECTION OF TRADITIONAL VALUES - Ekawati Marhaenny Dukut; Nuki Dhamayanti (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
The world of literature can be a medium of expressing the writer's expressions and ideas. Universal topics such as, love, death, and war often become subject mailers in the world of literature. In the novel, of The Color Purple. Alice Walker describes the oppression experienced by Afro American women in the female characters of Celie, Nellie, Shug Avery, Sofia, and Mary Agnes who faced sexual discrimina!ions in a patriarchal society. Womanhood, education, and lesbianism are factors that help the Afro American women to free themselves from traditional values. The Color Purple puts into words the process of its main character, Celie, who tries to reject and escape from the male domination of her world. The other Afro American women characters that help Celie to find her selfidentity represent the manifestation of the rejection of the traditional values. This article. which uses the socio-historical alld feminism approach. is intended to analyse the Afro-American women's rejection of traditional values by focusing on the major character of' Walker's The Color Purple. Celie. as she develops from being a victim of traditional values to the rejoiceful discovery of her selfidentity.